Restrukturisasi Pendidikan Menuju Bangsa Berkarakter - Mustofa Kamal (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2014)
National development priorities as outlined in the National Long-Term Development Plan (RPJP) for 2005 - 2025 (Law No. 17 of 2007), among others, are in realizing a society that is noble, moral, ethical, cultured, and civilized based on the philosophy of Pancasila